Irresistibly yours eaudiobook - Layne, Lauren (Oxford, 2015)
Hotshot sports editor Cole Sharpe has been freelancing for Oxford magazine for years, so when he hears about a staff position opening up, he figures that he's got the inside track. Then his boss drops a bombshell: Cole has competition. Female competition, in the form of a fresh-faced tomboy who can hang with the dudes and write circles around them, too. Penelope Pope knows all too well that she comes off as just one of the guys. Since she's learned that wanting more usually leads to disappointment, Penelope is resigned to sitting on the sidelines when it comes to love. So why does Cole make her want to get back in the game? The man is as arrogant as he is handsome. He probably sees her as nothing more than a barrier to his dream job. But when an unexpected kiss turns into a night of irresistible passion, Penelope has to figure out whether they're just fooling around or starting something real. Contains mature themes.